2018
DOI: 10.22435/blb.v14i2.196
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis pada Tikus Endemis Sulawesi (Rodentia: Muridae) dan Potensi Penularannya Antar Tikus dari Provinsi Sulawesi Selatan

Abstract: Leptospirosis merupakan penyakit zoonosis disebabkan bakteri Leptospira patogenik dan berpotensi menyebabkan kematian pada manusia. Tikus sebagai reservoir utama Leptospira kebanyakan diteliti di kawasan perkotaan atau pedesaan di sekitar permukiman. Sebaliknya, penelitian leptospirosis pada tikus endemis jumlahnya sedikit. Penelitian ini bertujuan untuk mengidentifikasi jenis tikus endemis Sulawesi sebagai reservoir Leptospira di Kabupaten Bulukumba, Pangkep dan Luwu Timur. Penelitian ini merupakan bagian dar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Knowing that farmers are very close to this kind of environment then the preventive effort is required as well as the socialization to the preventive behavior of Leptospirosis. 20 Open access under CC-BY-NC-SA 4.0 International License Age factor in this research has no relationship to the preventive behavior. The result is different to Hasanah, Nugraheni and Wahyuni's.…”
Section: Resultsmentioning
confidence: 75%
“…Knowing that farmers are very close to this kind of environment then the preventive effort is required as well as the socialization to the preventive behavior of Leptospirosis. 20 Open access under CC-BY-NC-SA 4.0 International License Age factor in this research has no relationship to the preventive behavior. The result is different to Hasanah, Nugraheni and Wahyuni's.…”
Section: Resultsmentioning
confidence: 75%
“…The results indicated that various endemic rats such as R. marmosurus, R. hoffmanni, B. chrysocomus, B. andrewsi and B. coelestis were infected with leptospirosis (Ardanto et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…The test for leptospirosis in the laboratory showed that the most vulnerable species to be exposed to leptospirosis was R. tanezumi or domestic rats. Several studies have also shown that cases of leptospirosis were found in rats near residential areas (Ardanto et al, 2018;Farida et al, 2006;Ikawati et al, 2013b). Human activities in the forest, such as collecting woods, hunting, and ecotourism activities could increase the risk of the transmission of leptospirosis to humans.…”
Section: Discussionmentioning
confidence: 98%
“…Then the use of the Lip32 gene as a primer is able to detect pathogenic leptospira bacteria. But this method has not been able to detect serovar-level leptospira [18].…”
Section: Discussionmentioning
confidence: 99%